Tax evasion by firms - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2021)
This contribution surveys theoretical analyses of tax evasion by firms. It uses a simple model in which the firm determines economic activity and the under-declaration of the tax base to integrate various approaches into a coherent analytical framework. Initially, the chapter characterises the basic features of the firm's decision. Subsequently, it considers the effects of firm-size heterogeneity, restrictions on evasion behaviour, the co-existence of tax evasion with other illegal activities, output market interactions, non-profit objectives, and corporate governance issues.
Keywords: H25; H26; K34; 330; Firm; Tax Avoidance; Tax Evasion